The Contribution of Neutrophils to the Pathogenesis of RSV Bronchiolitis - Ismail Sebina; Simon Phipps (Viruses, 2020)
Acute viral bronchiolitis causes significant mortality in the developing world, is the number one cause of infant hospitalisation in the developed world, and is associated with the later development of chronic lung diseases such as asthma. A vaccine against respiratory syncytial virus (RSV), the leading cause of viral bronchiolitis in infancy, remains elusive, and hence new therapeutic modalities are needed to limit disease severity. However, much remains unknown about the underlying pathogenic mechanisms. Neutrophilic inflammation is the predominant phenotype observed in infants with both mild and severe disease, however, a clear understanding of the beneficial and deleterious effects of neutrophils is lacking. In this review, we describe the multifaceted roles of neutrophils in host defence and antiviral immunity, consider their contribution to bronchiolitis pathogenesis, and discuss whether new approaches that target neutrophil effector functions will be suitable for treating severe RSV bronchiolitis.